2015
DOI: 10.1177/1365480215589662
|View full text |Cite
|
Sign up to set email alerts
|

The voice of youths about school and its mark on their lives

Abstract: The work we present is a qualitative study of the school experience and its repercussions on the current lives of ex-students from Mallorca. The work has two purposes: (a) to learn about the school's influence on the identity development of the students and (b) to incorporate the voices of former students regarding their reflection on the present and with a look towards the future and the challenges they face. The study is part of the movement known as Student Voice, which considers students to be valuable exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…School has long-lasting effects on students' development, even when students were in outside of schools. Furthermore, it can only happen when the school listens to the meaning communicated by students (Pomar & Pinya, 2015). Research conducted in Norwegian schools has shown that students want to be heard.…”
Section: Discussionmentioning
confidence: 99%
“…School has long-lasting effects on students' development, even when students were in outside of schools. Furthermore, it can only happen when the school listens to the meaning communicated by students (Pomar & Pinya, 2015). Research conducted in Norwegian schools has shown that students want to be heard.…”
Section: Discussionmentioning
confidence: 99%